A foaming material prepared by de-crosslinking and recycling of EVA waste, and its manufacturing method and application
The solution expansion method is used to de-link EVA waste and re-used it for foaming materials, which solves the problem of difficulty in recycling and reuse of EVA waste, and achieves efficient recycling and performance improvement.
Patent Information
- Application Number
- CN202311320866.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-10-12
AI Technical Summary
Due to the highly crosslinked three-dimensional network structure, EVA waste is difficult to effectively recycle and reuse, resulting in waste of resources and environmental pollution.
2,2' dithiodibenzoic acid is uniformly penetrated into the three-dimensional network of EVA waste by solution expansion method, de-crosslinking of the EVA waste and re-utilizing it into the foaming material, introducing new functional groups to improve the network structure.
It realizes efficient recycling and reuse of EVA waste, improves the foaming ratio, mechanical strength and dimensional stability of foamed materials, and reduces environmental pollution and resource waste.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of foaming materials, in particular to a method for preparing foaming materials based on de-crosslinking and recycling of EVA waste and its application. Technical Background
[0002] With the rapid development of industry and social economy, people have more and more demands for cushioning and rebound materials (such as soles), and EVA foam materials have been widely used. However, in the production process of EVA foam materials and other products, due to the needs of size and shape, a large amount of scraps and defective materials will inevitably be produced. Most of these wastes are cross-linked. Due to the complex composition of EVA foam products, it is difficult to achieve efficient recycling and reuse. Most of them are treated by incineration, resulting in a lot of waste and environmental pollution, which is contrary to my country's basic national policy of saving resources and protecting the environment. Therefore, the recycling and reuse of EVA waste is practical. Because the recycling of EVA waste can effectively reduce the impact on the environment. Secondly, in terms of saving raw materials and reducing costs, recycling and reuse of EVA materials is also very important. Recycling and reuse can reduce the demand for raw materials, reduce the use of fossil energy, reduce production costs, and is conducive to the sustainable development of enterprises.
[0003] However, the molecular chains of EVA foaming materials will form a highly cross-linked three-dimensional network structure during the foaming process. Although the highly cross-linked three-dimensional network structure can give the foaming material the characteristics of heat resistance, corrosion resistance, and infusibility, these characteristics also lead to the difficulty of recycling and reusing EVA waste, and the poor recycling effect. The traditional recycling method through simple high-temperature shearing, because the free radicals generated during the high-temperature shearing process will collide with other active groups and form new macromolecular segments and three-dimensional network structures. This leads to poor de-crosslinking effect of EVA waste and low recovery rate.
[0004] Based on the above problems, the present invention uses a solution expansion method to uniformly infiltrate 2,2' dithiodibenzoic acid into the three-dimensional network of EVA waste. In the process of de-crosslinking of EVA waste, 2,2' dithiodibenzoic acid can generate sulfur free radicals and combine with free radicals generated by the destruction of the EVA network. This will effectively reduce the problem of free radicals generated by the destruction of the EVA network and forming new macromolecular segments and three-dimensional network structures. At the same time, new functional groups are introduced into the molecular chains of the de-crosslinked EVA, which is beneficial to the design of the network structure during the reuse process. On the other hand, the de-crosslinked EVA is reused in the foaming material, which can not only play a reinforcing role of the filler and improve the mechanical properties and foaming rate of the foaming material, but also the carboxyl groups on the de-crosslinked EVA molecular chains can form ionic bonds with Zn ions during the foaming process, further improving the dimensional stability of the foaming material. The effective recycling and reuse of EVA waste is achieved through a simple processing technology, which provides ideas for solving the problems of environmental and resource waste caused by EVA waste. Summary of the invention
[0005] In view of this, the present invention aims at the deficiencies in the prior art, and its main purpose is to provide a method and application of preparing a foaming material based on de-crosslinking and recycling of EVA waste, which has the characteristics of high foaming ratio, high mechanical strength and simple preparation process.
[0006] The present invention can be achieved through the following technical solutions:
[0007] A foaming material prepared by de-crosslinking and recycling EVA waste is prepared from the following components in parts by weight: 50-100 parts of ethylene-vinyl acetate copolymer (EVA), 0-50 parts of EVA waste, 1.5-5 parts of a foaming agent, 0.3-3 parts of a crosslinking agent, 3-10 parts of 2,2'-dithiodibenzoic acid, 5-20 parts of other additives and an appropriate amount of solvent.
[0008] To further achieve the purpose of the invention, preferably, the EVA is obtained by copolymerization of ethylene and vinyl acetate (VA), wherein the content of VA is 26%.
[0009] Preferably, the EVA waste is a flake material, and the VA content is 26%.
[0010] Preferably, the cross-linking agent is dicumyl peroxide (DCP).
[0011] Preferably, the blowing agent is azodicarbonamide (AC).
[0012] Preferably, the solvent is xylene.
[0013] Preferably, the other additives are ethylene octene copolymer (POE), talc, calcium carbonate, zinc stearate (ZnSt), zinc oxide (ZnO), stearic acid (Hst), styrene butadiene rubber (SBR) and butadiene rubber (BR).
[0014] The foaming material prepared by de-crosslinking and recycling EVA waste is characterized by comprising the following steps:
[0015] Step 1: Place the EVA waste in a xylene solution containing 2,2' dithiodibenzoic acid to expand the three-dimensional network of the EVA waste, and allow the 2,2' dithiodibenzoic acid to evenly penetrate the three-dimensional network. Then, dry at 40°C-60°C to constant weight.
[0016] Step 2: crush the EVA waste dried in step 1 with a pulverizer, and then sieve out the EVA powder with a 30-50 mesh sieve. Finally, put the EVA waste powder into a twin-screw extruder, set the temperature to 180°C-200°C, set the speed to 90r / min, and use the high temperature and high-speed shearing effect of the twin-screw extruder to obtain the de-crosslinked EVA waste.
[0017] Step 3: Put the de-crosslinked EVA waste, pure EVA, foaming agent, crosslinking agent and other additives in a torque rheometer at a temperature of 105°C and a speed of 60r / min in proportion and blend for 3-5 minutes. Then mix evenly on an open mill at 105°C. Finally, put it on a flat vulcanizer at 190°C for foaming for 5-8 minutes to obtain a foamed material.
[0018] Compared with the prior art, the present invention has the following advantages and effects:
[0019] 1) The present invention uses a solution expansion method to uniformly infiltrate 2,2' dithiodibenzoic acid into the three-dimensional network of EVA waste. During the de-crosslinking process of EVA waste, 2,2' dithiodibenzoic acid can generate sulfur free radicals that combine with free radicals generated by the destruction of the EVA network. This will effectively reduce the problem of free radicals generated by the destruction of the EVA network forming new macromolecular segments and three-dimensional network structures, and at the same time introduce new functional groups into the molecular chains of the de-crosslinked EVA, which is beneficial to the design of the network structure during the reuse process.
[0020] 2) The present invention uses the recycled EVA waste to replace part of the pure EVA in the foaming material, which not only strengthens the mechanical properties of the foaming material and improves the foaming ratio of the foaming material, but also introduces new functional groups. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Table 2 shows the self-healing test results of Examples 1-5 and Comparative Example 2. DETAILED DESCRIPTION
[0022] The present invention discloses a foaming material prepared by crosslinking and recycling EVA waste, which is prepared from the following components in parts by weight: 50-100 parts of ethylene-vinyl acetate copolymer (EVA), 0-50 parts of EVA waste, 1.5-5 parts of foaming agent, 0.3-3 parts of crosslinking agent, 3-10 parts of 2,2' dithiodibenzoic acid, 5-20 parts of other auxiliary agents and an appropriate amount of solvent. In order to better describe the specific implementation effect of the present invention, preferably, the crosslinking agent is dicumyl peroxide (DCP), the foaming agent is azodicarbonamide (AC), the solvent is xylene, and the other auxiliary agents are ethylene-octene copolymer (POE), talcum powder, zinc stearate (ZnSt), zinc oxide (ZnO), stearic acid (Hst), styrene-butadiene rubber (SBR) and butadiene rubber (BR).
[0023] The present invention discloses a method for preparing a foaming material based on de-crosslinking and recycling of EVA waste, comprising the following steps:
[0024] Step 1: Place the EVA waste in a xylene solution containing 2,2' dithiodibenzoic acid to expand the three-dimensional network of the EVA waste, and allow the 2,2' dithiodibenzoic acid to evenly penetrate the three-dimensional network. Then, dry at 40°C-60°C to constant weight.
[0025] Step 2: crush the EVA waste dried in step 1 with a pulverizer, and then sieve out the EVA powder with a 30-50 mesh sieve. Finally, put the EVA waste powder into a twin-screw extruder, set the temperature to 180°C-200°C, set the speed to 90r / min, and use the high temperature of the twin-screw extruder and the high-speed shearing effect of the rotor to obtain the de-crosslinked EVA waste.
[0026] Step 3: Put the de-crosslinked EVA waste, pure EVA, foaming agent, crosslinking agent and other additives in a torque rheometer at a temperature of 105°C and a speed of 60r / min in proportion and blend for 3-5 minutes. Then mix evenly on an open mill at 105°C. Finally, put it on a flat vulcanizer at 190°C for foaming for 5-8 minutes to obtain a foamed material.
[0027] The invention discloses an application of preparing a foaming material based on the de-crosslinking and recycling of EVA waste, and the foaming material is applied to foaming shoe materials and sound insulation materials.
[0028] The present invention is described in detail with multiple examples below:
[0029] Preparation of de-crosslinked EVA (ReEVA)
[0030] Cut 10g of EVA flake waste and put it into 200ml of xylene, then add 1g of 2,2' dithiodibenzoic acid and soak them together for 3 days, then dry them in a 40℃ oven to constant weight. Crush the dried EVA waste with a pulverizer, and then sieve out the EVA powder with a 30-50 mesh sieve. Finally, put the EVA waste powder into a twin-screw extruder, set the temperature to 200℃, set the speed to 90r / min, and high-speed shear for 15 minutes to obtain ReEVA.
[0031] Example 1 (Examples 1-5 differ in the amount of ReEVA added, which are 5, 10, 15, 20 and 25 g, respectively).
[0032] 65g pure EVA, 5g ReEVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0033] Example 2
[0034] 60g pure EVA, 10g ReEVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0035] Example 3
[0036] 55g pure EVA, 15g ReEVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0037] Example 4
[0038] 50g pure EVA, 20g ReEVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0039] Example 5
[0040] 45g pure EVA, 25g ReEVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0041] Comparative Example 1 (without adding ReEVA)
[0042] 70g pure EVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in a foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0043] Comparative Example 2 (REVA is obtained by direct high temperature shearing and cross-linking without solution expansion)
[0044] 55g pure EVA, 15g REVA, 3.5g SBR, 3.5g BR, 14g POE, 14g talc, 0.42g HSt, 0.7g ZnSt, 1.4g ZnO, 0.77g DCP and 2.38g AC were sequentially put into a torque rheometer at a temperature of 105°C and a speed of 60r / min and blended for 3 minutes. Then, the mixture was taken out and mixed evenly on an open mill at a temperature of 105°C. Finally, the foaming material was foamed in the foaming mold cavity of a flat vulcanizer at 190°C for 7 minutes.
[0045] Performance Testing
[0046] A universal tester was used to perform a tensile test on the foamed materials obtained in Example 1 to Example 5 at room temperature to detect the tensile strength and elongation at break of the samples, wherein:
[0047] The sample size is 60*10 mm (length*width), the initial test distance between the two fixtures is 20 mm, the sample is tested at a loading speed of 50 mm / min, and 3 samples are provided for each embodiment.
[0048] The tensile rate of the tear strength test was set at 500 mm / min, and a trouser-type specimen was used for the test. Each sample was tested at least 3 times.
[0049] The sample for the compression strength test was cut into a cuboid of 25 mm in length × 25 mm in width × 20 mm in height. The compression rate used in the test was 100 mm / min, and the compression amount was 50%.
[0050] Get the compressive strength.
[0051] The resilience test was carried out using a vertical resilience tester. Five positions were selected on each sample for the resilience test. Each position was tested five times, and the average value was taken to obtain the resilience of the foam material.
[0052] Table 1 The tensile strength, elongation at break, tear strength, compressive strength and resilience of Examples 1-5 and Comparative Examples 1-2 were tested, and the results are shown in the following table:
[0053]
[0054] It can be seen from Table 1 that in Examples 1-5, as the ReEVA content increases, the tensile strength, elongation at break, tear strength, compressive strength and resilience of the foamed material first increase and then decrease. Among them, when the ReEVA content is 15g, the mechanical properties of the foamed material, elongation at break, tear strength, compressive strength and resilience reach the best, which are better than the comparative samples of Comparative Examples 1 and 2, which are 2.12MPa, 405.3%, 7.8kN / m, 0.28MPa and 52.5% respectively. It can be seen from the above results that compared with REVA obtained by direct high-temperature shearing, ReEVA has more advantages in improving the performance of the foamed material. However, when more than 15g of ReEVA is added, the various properties of the foamed material decrease. This may be because too much ReEVA is poorly dispersed in the matrix, causing the uniformity of the matrix to deteriorate.
[0055] The self-healing experiment was conducted using dumbbell-shaped specimens. First, the sample was cut from the middle with a scalpel, and then the two sections were fully spliced together and then healed at 60°C. After a certain period of healing, the tensile properties were tested at the same tensile rate, and at least three specimens were tested for each group of samples. The self-healing efficiency was calculated using the following formula:
[0056]
[0057] ε healed is the tensile strength after healing, ε original is the original tensile strength.
[0058] See the attached drawings for details. Figure 1 , Figure 1 The self-healing of Examples 1-5 and Comparative Example 2 was tested.
[0059] from Figure 1 It can be seen that by incorporating a new functional group carboxyl in ReEVA and applying it to the foaming material, a dynamic ionic bond can be formed, thereby giving the foaming material the function of self-healing. Compared with the foaming material with added REVA, the self-healing efficiency of Example 3 is as high as 86%. However, when the amount of ReEVA added is too much, the self-healing efficiency tends to decrease. This may be because the excess ReEVA is unevenly distributed in the matrix and the resistance to the movement of the molecular chain increases.
[0060] Take samples of the foam material at three different locations and test them on a specific gravity balance. Take the average value to obtain the density ρ (g / cm 3 ).
[0061] The calculation method of foam expansion ratio (FER) is shown in the formula.
[0062]
[0063] ρ Before —Density of the blended rubber before foaming,
[0064] ρ After —Density of the product after foaming.
[0065] Table 2 The density and expansion ratio of Examples 1-5 and Comparative Examples 1-2 can be calculated, and the results are shown in the following table:
[0066] Sample name <![CDATA[Density (g / cm 3 )]]> Foaming ratio Example 1 0.156 6.47 Example 2 0.166 6.44 Example 3 0.159 6.56 Example 4 0.157 6.63 Example 5 0.154 6.72 Comparative Example 1 0.152 6.51 Comparative Example 2 0.164 6.38
[0067] As can be seen from the table, compared with comparative example 1, the addition of ReEVA effectively increases the foaming rate of the foaming material. In addition, compared with comparative example 2 with the same content, example 3 has a higher foaming ratio (6.56). This shows that the reuse of ReEVA is more advantageous than REVA.
[0068] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should all be equivalent alternatives and are included in the scope of protection of the present invention.
Claims
1. A foaming material prepared by de-crosslinking and recycling EVA waste, characterized in that: The raw material components thereof are respectively as follows by weight: 50-100 parts of ethylene-vinyl acetate copolymer (EVA), 0-50 parts of EVA waste, 1.5-5 parts of foaming agent, 0.3-3 parts of crosslinking agent, 3-10 parts of 2,2' dithiodibenzoic acid, 5-20 parts of other auxiliary agents and an appropriate amount of solvent, wherein the solvent is xylene. The preparation method of the foaming material comprises preparing de-crosslinked EVA waste; the steps of preparing the de-crosslinked EVA waste comprise putting the EVA waste into a xylene solution containing 2,2' dithiodibenzoic acid to expand the three-dimensional network of the EVA waste, and the 2,2' dithiodibenzoic acid uniformly permeates the three-dimensional network; the de-crosslinked EVA waste reacts with EVA, the foaming agent, the crosslinking agent and other auxiliary agents to obtain the foaming material.
2. The foaming material prepared by de-crosslinking and recycling EVA waste according to claim 1, characterized in that: The EVA is obtained by copolymerization of ethylene and vinyl acetate, wherein the content of VA is 26%.
3. The foaming material prepared by de-crosslinking and recycling EVA waste according to claim 1, characterized in that: The EVA waste comes from waste packaging materials, shoe materials and toys that are broken into flakes.
4. The foaming material prepared by de-crosslinking and recycling EVA waste according to claim 1, characterized in that: The cross-linking agent is one or more of dicumyl peroxide, dibenzoyl peroxide or peroxy-2-ethylhexyl tert-butyl carbonate.
5. The foaming material prepared by de-crosslinking and recycling EVA waste according to claim 1, characterized in that: The foaming agent is one or more of azodicarbonamide, sodium bicarbonate or ammonium bicarbonate.
6. The foaming material prepared by de-crosslinking and recycling EVA waste according to claim 1, characterized in that: The other auxiliary agents are ethylene-octene copolymer, talcum powder, calcium carbonate, zinc stearate, zinc oxide, stearic acid, styrene-butadiene rubber and butadiene rubber.
7. A method for preparing a foaming material based on de-crosslinking and recycling of EVA waste as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Place the recycled EVA waste into a xylene solution containing 2,2' dithiodibenzoic acid to expand the three-dimensional network of the EVA waste, and allow the 2,2' dithiodibenzoic acid to evenly penetrate the three-dimensional network for 12 hours, and then dry in an oven at 40-60°C to constant weight; Step 2: crush the EVA waste dried in step 1 with a pulverizer, then sieve out the EVA powder with a 30-50 mesh sieve, and finally put the EVA waste powder into a twin-screw extruder, set the temperature to 180°C-200°C, set the speed to 90 r / min, and use the high temperature of the twin-screw extruder and the high-speed shearing effect of the rotor to obtain the de-crosslinked EVA waste; Step three, the de-crosslinked EVA waste, EVA, foaming agent, crosslinking agent and other additives are placed in a torque rheometer at a temperature of 105°C and a speed of 60 r / min in proportion and blended for 3-5 minutes, then mixed evenly on an open mill at 105°C, and finally placed on a flat vulcanizer at 190°C for foaming for 5-8 minutes to obtain a foamed material.
8. An application of a foaming material prepared by de-crosslinking and recycling EVA waste as claimed in any one of claims 1 to 6, characterized in that: It is used in foamed shoe materials and sound insulation materials.
Citation Information
Patent Citations
EVA foamed plastic regeneration granulation method
CN113372645A
Preparation method of recyclable EVA / PVA (Ethylene Vinyl Acetate / Polyvinyl Acetate) foaming material and foaming material
CN115073844A